Seasonal effects of major primary pollutants in Ali Sabah Al-Salem residential area in Kuwait. (1st January 2015) - Al-Awadi, Layla T.; Popov, Viktor; Khan, A.R.
Air quality data consisting of various pollutants (PM10, SO2, NO2, O3, CO, NonCH4 hydrocarbon) were collected for a year and its seasonal influence was investigated in detail. The number of exceedances of all the pollutants based on Kuwait Environmental Public Authority (EPA) standards was examined. The seasonal variation of hourly averages of (O3 ), (CO) and (NO) are presented as midweek and/or weekend effects to reveal noticeable deviations. Ozone generation and accumulation rate during the high ozone period (April to September) was analysed to reveal weekend effect reflecting volatile organic compound (VOC) sensitive region (abundance of NOx relative to the VOCs) for the specified period at Ali Sabah Al-Salem (ASA) residential area. A decrease in NOx emission strongly influenced O3 production and accumulation. Flares in the neighbouring petroleum refineries and petrochemical industries and two adjacent highways with high traffic density have contributed to the NOx emissions in the area.